2017
DOI: 10.1016/j.fuel.2016.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-velocity non-Darcy flow on well production performance in shale and tight oil reservoirs

Abstract: There are many core flooding studies showing that the liquid-measured permeability is lower than the Klinkenberg-corrected gas permeability. The flow velocity in a low pressure gradient regime is lower than what is estimated from Darcy's law. This phenomenon is considered as low-velocity non-Darcy flow in the literature. Besides, many researchers believe that there is a threshold pressure gradient (TPG) that needs to be overcome before the fluid flow can occur. The related results in the literature are critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(71 citation statements)
references
References 18 publications
0
70
0
1
Order By: Relevance
“…It is difficult to obtain the analytical solution of the partial differential equation with a strong nonlinear term and variable coefficient. So, the finite difference method [16] is used to solve the model of the volume fracturing vertical well considering the stress sensitivity and low-velocity non-Darcy flow. The flow coefficient term is treated explicitly and changed with the pressure.…”
Section: Geofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to obtain the analytical solution of the partial differential equation with a strong nonlinear term and variable coefficient. So, the finite difference method [16] is used to solve the model of the volume fracturing vertical well considering the stress sensitivity and low-velocity non-Darcy flow. The flow coefficient term is treated explicitly and changed with the pressure.…”
Section: Geofluidsmentioning
confidence: 99%
“…In other words, the fracture and reservoir all are stress sensitivity medium [12][13][14]. In addition, due to the tiny porous and ultralow permeability of tight reservoirs, the flow in tight reservoirs obeys the law of low-velocity non-Darcy flow instead of Darcy flow [15], which is the fact that the flow velocity in a low pressure gradient regime is lower than what is estimated from Darcy's law [16].…”
Section: Introductionmentioning
confidence: 96%
“…It is well known Darcy flow assumes that the flow velocity-pressure gradient relationship is a straight line which passes through the origin. Recently, many non-Darcy flow phenomena are found in low-permeability media [1,2], tight carbonate oil and gas reservoirs [3], shale oil and gas reservoirs [4,5], and clay soil [6]. Non-Darcy flow indicates that the flow velocity-pressure gradient relationship is not a straight line, also called nonlinear flow in porous media.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Experiments also were conducted to measure the thickness of boundarylayers and investigate the effect of boundary-layer on effective liquid permeability. 6,[11][12][13][14][15][16] The experiment results showed that the thickness of boundarylayer is related to pressure gradient, fluid viscosity, pore radius and fluid type. 11 With nanoscale simulation using dissipative particle dynamics and experimental data published in literatures, Cao et al 9 proposed an empirical equation to calculate boundary-layer thickness, and assuming that pore size distribution can be represented with Gaussian function, the authors developed a permeability model for tight oil reservoirs coupling boundarylayer effect.…”
Section: Introductionmentioning
confidence: 99%